Social impact measurement in a nonprofit organization: Lessons learned from impact measurement based on Social Return on Investment (SROI) in Bagázs Association - Révész, Éva; Dőry, Boglárka; Both, Emőke (Vezetéstudomány / Budapest Management Review, 2025)
The study concentrates on the Social Return on Investment, a widely recognized impact measurement tool, and aims to explore how and for what purposes an NGO might use the SROI calculation. The authors position the SROI method in the context of other social impact measurement tools, and they provide a description of its objectives, advantages,and limitations. The research is based on a longitudinal analysis of a case study of a Hungarian non-profit organization: the authors analyze the SROI applications of the Bagázs Association in 2016 and 2021. The results indicate that the SROI calculation provides valuable and communicable results for various stakeholder groups. The paper outlines the technical and methodological problems organizations could face while implementing SROI and suggests potential solutions.